Remote Learning During COVID-19 in Hisar School - Nahcivan, Lara; Çermik, Erkan (Open Schools Journal for Open Science, 2020)
In response to the COVID-19 pandemic, schools around the world have had to implement remote learning practices. The purpose of this study was to examine the attitudes of students towards the remote learning practices adapted by Hisar School during the COVID-19 pandemic. Three questionnaires with questions that asked students to reflect on their motivation levels, ability to complete assignments on time, contact their teachers, access school resources and other learning activities were sent to the entire high-school population of Hisar School. Our findings demonstrate that Hisar high school students had positive attitudes regarding the remote learning practices of their school, although 12th grade students had the lowest motivation scores and consequently lower positive attitudes. Additionally, students had difficulty accessing the school library’s online resources. Lastly, students preferred to complete assignments at their own pace rather than in predetermined self-study hours.